BUSINESS PLAN: Recomiendame - Olivares Amigo, Alan (2016)
Recomiendame is seeking funding of US$163,000 for launching our platform, by offering 40% of equity. This investment alongside founders’ capital will be used to implement business activities, develop and release our unique online platform of trusted service providers for Chilean market, which is expected to produce net profit of US$1.2 million yearly by 2020. We have planned an exit strategy of selling business at 5th year of trading, whereby Recomiendame equity value will be nearly US$3 million and minimum return for investors of US$1.2 million. In this Business Plan has been arranged most of business endeavours, including environmental and market analysis, strategies, plan and model, financial and risk analysis. We strongly believe that those, flexibility and continuous innovation will allow to become a leader in online directory for services market and the first choice of consumers.